Convict Depot - Carrera Isle - Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co.,[Trinidad and Tobago];Printed in Germany, 2011)
The postcard shows Carrera Island, referred to as Convict Depot because during the 1800s prisoners were carried to the island to quarry limestone for road building. In 1877, a prison was constructed, today the island remains a prison island.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Prisons--Trinidad and Tobago; Islands--Trinidad and Tobago; Carrera Island